Online Customer Review, Online Customer Rating Dan Positioning Serta Dampaknya Terhadap Customer Trust Produk Somethinc (Studi Pada Pengguna Produk Somethinc di Kota Malang) - Venni Dwi Silfiani; Nur Hidayati; M Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to determine how the influence of Online customer  review, Online customer  rating, and Positioning on Customer  trust. The population in this study were users of SomeThinc products in Malang City. The Non-Probability Sampling method is Snowball Sampling with a sample of 60 respondents. The results of the study partially show that: 1) There is a positive and significant influence Online customer  review on the Customer  trust of Somethinc products 2) There is a positive and significant influence of Online customer  rating on the Customer  trust of Somethinc products 3) There is a positive and significant influence of Positioning on the Customer  trust of Somethinc products. All independent variables have a simultaneous effect on the Customer  trust of SomeThinc products. Keywords: Online customer  review, Online customer  rating, Positioning and Customer  trust